Penerapan Metode Tutor Sebaya untuk Meningkatkan Hasil Belajar Mata Pelajaran Matematika Materi FPB dan KPK pada Siswa Kelas IV SDN 1 Langkapura - Mardiana, Mardiana (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
: The teacher's habit of using the lecture method in mathematics makes students less enthusiastic and less motivated to take part in learning. This is because when learning takes place, teacher centered activities, while students only listen to the material delivered by the teacher. With methods that are less varied and only rely on teachers in learning, many students experience difficulties in learning mathematics, especially in FPB and KPK material. Based on these problems, the solution chosen was to apply the peer tutor method, guided by peer tutors, then students were expected to be able to solve questions related to FPB and KPK. The formulation of the problem of this research is whether through the application of the peer tutor method can improve mathematics learning outcomes for fourth grade students of SDN 1 Langkapura for the 2018/2019 academic year? The purpose of this study was to improve the mathematics learning outcomes of determining FPB and KPK for grade IV SDN 1 Langkapura students. This type of research is classroom action research. The subjects of this study were 40 grade students of SDN 1 Langkapura for the 2018/2019 academic year, with a total of 40 students consisting of 21 male students and 19 female students. Data collection techniques used test and non-test techniques. This classroom action research was conducted in 2 cycles, each consisting of 2 meetings. Each meeting consists of 4 stages, namely planning, implementing, observing, and reflecting. The results showed that students' completeness in classical learning increased from 57.5% in the pre-cycle to 70% in the first cycle and increased again to 85% in the second cycle. The data has reached the set success indicator, which is 85%. The average score of the students' formative tests increased from 58.0 in the pre-cycle stage to 69.75 in the first cycle and to 76.50 in the second cycle. These data have reached an indicator of research success, namely the average score of students â‰¥ 60. The number of students who scored above the KKM has also increased. In the pre-cycle stage there were 23 students or 57.5%, increasing in the first cycle to 28 students or 70% and again experiencing an increase in the second cycle to 34 students or 85%. This data has reached an indicator of research success, namely the number of students who score above the KKM by 75%. The conclusion of this research is that through the application of the peer tutor method in learning mathematics can improve teacher skills, student activities, and student learning outcomes of Class IV SDN 1 Langkapura for the 2018/2019 academic year. Suggestions are given that teachers should use innovative models and varied media in learning.